Pengembangan Media Pembelajaran Pengetahuan Tekstil Berbasis Aplikasi Android - Romadhona Chusna Tsani; Muhammad Wahyu Gunawan (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
The aim of the research is to find out the process of developing knowledge learning media based on Android applications.Learning media is very much needed as a tool used in practical learning.Changes in educational progress require innovation in learning media to keep them up to dat and able to overcome new problems that arise. The research method used is the R & D research and development method with the 4D model. The stages of the 4D development model are 1) Definition; 2) Design; 3) Development; 4) Distribution. This research produces android-based textile knowledge learning media. The software used is iSpring Suite Toolkit Authoring based on Power Point; and Website 2 APK Builder.The iSpring Suit software is used in the design and development of learning media, while the Website 2 APK Builder software is used to change Android application programs. Based on the results of the learning media feasibility questionnaire, it can be seen that the textile knowledge learning media is very feasible to use, reaching 90%.